Gone Tomorrow - Child, Lee (London Bantam Books, 2010)
Riding the subway in New York at two o'clock in the morning, Reacher knows the twelve giveaway signs to look out for. Watching one of his fellow-passengers, he becomes sharply aware: one by one, she ticks off every bulletpoint on his list
Keywords: Reacher, Jack (Fictitious character) -- Ex-police officers -- Conspiracies